To solve the equation \(-4 + 2b = -40\) using inverse operations, follow these steps:
Step 1: Isolate the term with the variable
First, we want to get the term with \( b \) (which is \( 2b \)) by itself on one side of the equation. To do this, we can add \( 4 \) to both sides of the equation.
\[ -4 + 2b + 4 = -40 + 4 \]
This simplifies to:
\[ 2b = -36 \]
Step 2: Solve for \( b \)
Next, we need to isolate \( b \) by dividing both sides of the equation by \( 2 \):
\[ \frac{2b}{2} = \frac{-36}{2} \]
This simplifies to:
\[ b = -18 \]
Step 3: Check your solution
To ensure our solution is correct, we can substitute \( b = -18 \) back into the original equation:
\[ -4 + 2(-18) = -40 \]
Calculating the left side:
\[ -4 - 36 = -40 \]
Since both sides of the equation are equal, our solution is verified.
Final Answer
The solution to the equation \(-4 + 2b = -40\) is:
\[ b = -18 \]
Note
Since I am unable to use a sketch pad, I've outlined the steps clearly. You can visualize or write this out on a sketch pad by illustrating each step as shown above or graphically representing the operations you performed.